A Picture is Worth a Thousand Keywords: Exploring Mobile Image-Based Web Searching. (2nd November 2008) - Tollmar, Konrad; Möller, Ted; Nilsved, Björn
Abstract : Using images of objects as queries is a new approach to search for information on the Web. Image-based information retrieval goes beyond only matching images, as information in other modalities also can be extracted from data collections using an image search. We have developed a new system that uses images to search for web-based information. This paper has a particular focus on exploring users' experience of general mobile image-based web searches to find what issues and phenomena it contains. This was achieved in a multipart study by creating and letting respondents test prototypes of mobile image-based search systems and collect data using interviews, observations, video observations, and questionnaires. We observed that searching for information based only on visual similarity and without any assistance is sometimes difficult, especially on mobile devices with limited interaction bandwidth. Most of our subjects preferred a search tool that guides the users through the search result based on contextual information, compared to presenting the search result as a plain ranked list.